Developing fluency in a language of tactile communication - Neil Tuttle; Susan Hillier (Frontiers Media S.A., 2023)
Touch has been an integral part of physiotherapeutic approaches since the inception of the profession. More recently, advances in the evidence-base for exercise prescription and "active" management have brought "touch" into question. This, in part, assumes that the patient or recipient simply passively receives the input rather than being an active partner in the interaction. In this article, we propose that touch can be used as a two-way conversation between therapist and client where each is engaged in tactile communication that has the potential to raise patient awareness and improve movement-based behaviour.